ANALISIS KUALITAS PELAYANAN DAN DAYA TARIK PASIEN RAWAT INAP TERHADAP KEPUASAN PELANGGAN DI RUMAH SAKIT UMUM FIKRI MEDIKA KARAWANG - Rustomo Rustomo; Junengsih Junengsih; Juli Yuliani (Universitas Nusa Cendana, 2022)
The Covid-19 pandemic period of the various risks that will be borne by the provision of health services is of particular concern to the public and the government. The people of Karawang Regency and its surroundings will focus on the management of these services. So this study aims to analyze directly the quality of service and how much attractiveness the patients have in order to continue to choose RSU Fikri Medika Karawang permanently for medical services for themselves and their families with perceived service satisfaction. The results of the distribution of the questionnaire to the respondents through the google questionnaire with the number of samples set at 100 respondents using the non-probability sampling quota technique. All questionnaires returned properly. The results of data analysis showed that the average patient who visited RSU Fikri Medika Karawang was young and female. Data processing with SPSS Version 24 showed that all data were valid and had a very good value for the consistency/consistency of the research instrument. Each variable of service quality and patient attractiveness has a strong impact on customer satisfaction, and has a strong contribution from the independent variable to the highly significant dependent variable. All alternative hypothesis tests accepted and rejected the Ho hypothesis in the significant test and the simultaneous test. Keywords: Service Quality, Attraction, Customer Satisfaction, Covid-19, Hospital